TIPOLOGI GRAMATIKAL DAN SISTEM PIVOT BAHASA PAKPAK-DAIRI - Ida Basaria (LITERA, 2013)
This study aims to describe the grammatical typology and pivot system of the Pakpak-Dairi language (PDL). The data were analyzed using the distribution method with substitution and transformation techniques. The pivot testing was carried out on coordinate and subordinate constructions, adverbial clauses, and non-finite verbal clauses. The findings show that grammatically PDL belongs to the accusative language typology.The pivot testing shows that the deletion of a nominal phrase in PDL can be directly made if it functions as a subject or adverbial. If a nominal phrase functions as a predicate, the deletion cannot be directly made; one of the clauses must be made passive or topicalized first. Based on such a pattern, in can be concluded that PDL belongs to the accusative language typology with a pivot pattern of S/A.